ON BOUNDED OPERATORS IN $L^p$ SPACES - Petrosyan, A.I.; Beknazaryan, A.F. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In the present paper the linear operators that depend on a normal pair of weight functions $\{φ, ψ,\}$ in the Banach spaces $L^p(D)$, where $D$ is the unit disk in the complex plane, are considered. It is investigated, for which values of p these operators are bounded.
Keywords: Banach space; analytic function; bounded operator